2012
DOI: 10.1098/rspb.2012.0376
|View full text |Cite
|
Sign up to set email alerts
|

Testing the independent species’ arrangement assertion made by theories of stochastic geometry of biodiversity

Abstract: The assertion that the spatial location of different species is independent of each other is fundamental in major ecological theories such as neutral theory that describes a stochastic geometry of biodiversity. However, this assertion has rarely been tested. Here we use techniques of spatial point pattern analysis to conduct a comprehensive test of the independence assertion by analysing data from three large forest plots with different species richness: a species-rich tropical forest at Barro Colorado Island … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
216
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(246 citation statements)
references
References 37 publications
22
216
3
4
Order By: Relevance
“…We can use this model to simultaneously fit the wavelet variance of two individual species and their covariance. However, in species-rich communities such as Barro Colorado, with ∼300 tree species in 50 ha, a dilution effect yields approximate species independence (Wiegand et al 2012). As a result, there is little improvement, if any, in fitting the multivariate model compared with fitting each species independently.…”
Section: Discussionmentioning
confidence: 99%
“…We can use this model to simultaneously fit the wavelet variance of two individual species and their covariance. However, in species-rich communities such as Barro Colorado, with ∼300 tree species in 50 ha, a dilution effect yields approximate species independence (Wiegand et al 2012). As a result, there is little improvement, if any, in fitting the multivariate model compared with fitting each species independently.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding various ecological mechanisms and processes that influence species assemblage are critical to get deep insights on species associations and community structure. Analyzing the spatial patterns of species are therefore of main interest in community ecology to figure out the underlying mechanisms and to test different ecological theories [2][3][4]. Several processes-such as competition or facilitation, dispersal limitation, habitat preference, Janzen-Connell hypothesis-that have been proposed for explaining community structure and species coexistence in species-rich forests are mainly based on spatial characteristics of species associations [5].…”
Section: Introductionmentioning
confidence: 99%
“…Species coexistence in diverse communities such as tropical forests can also be described by neutral theory, which assumes that species associations are assembled by dispersal limitation and demographic stochastics [15]. Similarly, previous studies suggested that stochastic dilution effect that assumes independent placement of individuals of different species can well explain species coexistence in tropical forests [3,16,17]. The stochastic dilution effect assumes hypotheses of intraspecific clustering, independence of interspecific interaction and abundance of species following a hollow curve distribution [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil characteristics can be strong 72 predictors of plant community composition (Gough et al, 2000;Tilman and Olff, 1991), 73 although the scale of the studies influences the predictive power of soil parameters like pH, 74 carbon, nitrogen or phosphorus content (Sebastiá, 2004). But not only abiotic factors are 75 influenced by the scale of a study; positive and negative species-species associations can occur 76 at small scales and disappear with increasing scale (Wiegand et al, 2012).…”
mentioning
confidence: 99%